Phenology and yield of maize for different sowing dates in a tropical mountain environment - Jaimez, Ramón (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2012)
Experimenta were carried out in order to examine the relationship between leaf appearance and thermal time under field conditions and to improve a model that simulates development and production of maize in tropical mountain environments. The comparative phenology and productivity of the tropical highland maize cultivar Santa Rosa were analized as a function of different sowing dates. The relationships between leaf appearance rate and thermal time for both sowings dates tended to be basically curvilinear and agreed with results shown in the literature. The number of leaves depended on daily maximum and minimum temperature variations and on the stage of plant growth. These affected the timing of anthesis and other development phases. The average yield and number of ears was constant for both sowing dates.